LEBARAN: AS MOMENTUM FOR STRENGTHEN INTER-ETHNIC HARMONY IN SEMPURNA VILLAGE - Wasis Suprapto; Sania Sania; dodik kariadi; Dina Anika Marhayani (STKIP Singkawang, 2024)
This article aims to examine three things, namely (1) the social life of the community in Sempurna Village, (2) a series of Eid traditions in Sempurna Village, and (3) the contribution of Eid traditions to strengthening harmony between ethnic groups in Sempurna Village. This article is studied using a descriptive research type. The subject of the research is the community in Sempurna Village. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study show that: (1) The name of the village is taken from the name of the palm oil company in the village, namely Sempurna. This village was officially established on May 31, 2001. Demographically, the Perfect Village has four different ethnic groups, namely Malay at 70%, Javanese at 15%, Sundanese at 10%, and Sasak at 5%. (2) Sempurna Village has traditions before Eid al-Fitr such as Paying Zakat Fitrah, Torch Parade, Takbiran, and Betandang. (3) The series of Eid traditions in Sempurna Village can actually strengthen integration between ethnic groups in the village